Cycloid Psychosis Comorbid with Prader–Willi Syndrome: A Case Series. Issue 7 (8th May 2019) - Singh, Deepan; Sasson, Arielle; Rusciano, Vanessa; Wakimoto, Yuji; Pinkhasov, Aaron; Angulo, Moris
Abstract: Psychosis is a relatively common psychiatric phenomenon seen in patients with Prader–Willi Syndrome (PWS). However, the presentation is atypical and difficult to classify within currently defined affective or psychotic disorders. This distinct presentation may be better understood as a phenomenon called "cycloid psychosis, " described as an episodic psychosis with rapid full recovery between episodes. This study retrospectively analyzed the cases of 12 patients with genetically confirmed PWS who presented to an ambulatory psychiatric center for a change in behavior consistent with psychosis. Each case was then assessed for symptoms of cycloid psychosis, bipolar disorder, depression with psychotic features, schizophrenia, and schizoaffective disorder. Out of the 12 patients, 11 (91.7%) met the currently described diagnostic criteria for cycloid psychosis. Of the 12 patients, 7 (58.3%) also met the diagnostic criteria for bipolar disorder, and 1 (8.3%) also met the diagnostic criteria for schizoaffective disorder. None of the patients met the criteria for schizophrenia or depression with psychotic features. The findings in this study suggest that cycloid psychosis and bipolar disorder may both be comorbid with PWS. Psychiatric comorbidities in patients with PWS are atypical and clinicians should be aware of conditions such as cycloid psychosis when managing this vulnerable population.